Assessing Higher-Order Thinking Skills in Mathematics through Project-Based Learning at Sekolah Menengah Chung Hwa, Brunei Darussalam. - Siti Hajar; Amirah Salleh (Lembaga Publikasi Ilmiah Nusantara, 2026)
Developing students’ higher-order thinking skills (HOTS) is a critical goal in mathematics education, as it enables learners to analyze, evaluate, and create solutions to complex problems. This study aimed to assess the effectiveness of Project-Based Learning (PjBL) in enhancing HOTS among secondary school students at Sekolah Menengah Chung Hwa, Brunei Darussalam. A mixed-methods approach was employed, combining quantitative and qualitative data. The study involved 60 students from grade 10, who participated in mathematics projects designed to promote critical thinking, problem-solving, and creative reasoning over a six-week period. Data collection included pre- and post-tests measuring HOTS, classroom observations, and student interviews to explore experiences and perceptions of PjBL. The quantitative results indicated a significant increase in HOTS scores after the intervention, with the average post-test score rising from 62.5 to 81.3. Qualitative analysis revealed that students were more engaged, collaborative, and reflective during the project activities, demonstrating the ability to apply mathematical concepts in real-world contexts. These findings suggest that integrating PjBL in mathematics instruction not only improves students’ cognitive skills but also fosters motivation and deeper understanding. The study highlights the potential of active, student-centered learning approaches to cultivate essential skills for the 21st century. Implications for curriculum design, teacher training, and future research on enhancing HOTS in mathematics are discussed.